Zones of influence for railway traffic ground-borne vibrations - Filip Pachla; Bartosz Radecki-Pawlik; Tadeusz Tatara (Archives of Civil Engineering)
The article presents selected results of the assessment of the harmfulness of building vibrations and the impact of railway traffic on people staying in buildings. The research presented in the article concerns a long-term field study. Field research was conducted in various locations and with the movement of various types of rolling stock. The results were the basis for determining the zones of influence of railway vibrations on the building structure. The criteria adopted in the research were the conditions of the impact of vibrations on the structure of buildings as well as the vibration comfort for people staying in buildings and passively perceiving vibrations. The paper presents the methodology of field research and selected results from the conducted research. The proposed zones vary depending on the type of trains (freight and passenger). The range of zones also depends on the structure of the building and human perception of passively perceived vibrations. All analyses carried out for the purposes of this work are in accordance with Polish regulations and were performed by an accredited laboratory for testing vibrations and deformations of buildings. The proposed zones were adopted for use in design and diagnostic practice regarding the impact of vibrations on buildings and people in buildings.